Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Membaca Siswa Kelas IV SD Negeri 106805 Manunggal - Sari, Nurul Walianda; Harahap, Syarifah Ainun; Putri, Nizmi (Medan Resource Center, 2024)
This study aims to analyze the effect of the Discovery Learning model on the reading abilities of fourth-grade students at SD Negeri 106805 Manunggal. The research employs a Quasi-Experimental design, involving two classes: an experimental class that implements the Discovery Learning model and a control class using conventional methods, with a total of 60 students. The study investigates: (1) whether the Discovery Learning model has a greater impact compared to conventional teaching methods; (2) whether students with higher reading abilities achieve better learning outcomes; and (3) whether there is an interaction between the Discovery Learning model and students' reading abilities in influencing their academic performance. The results indicate that the Discovery Learning model significantly enhances students' reading abilities. Students with higher reading proficiency demonstrated superior academic performance compared to those with lower reading skills. Furthermore, a significant interaction was observed between the Discovery Learning model and students' reading abilities, contributing to more optimal learning outcomes. These findings suggest that the Discovery Learning model is an effective instructional strategy for improving reading skills in elementary school students.